A review of the international Burn Injury Database (iBID) for England and Wales: descriptive analysis of burn injuries 2003–2011. Issue 2 (27th February 2015) - Stylianou, Neophytos; Buchan, Iain; Dunn, Ken W
Abstract : Objective: To describe, for the first time, distribution (by geography, age, sex) and time trends in burn injury in England and Wales over the period that the international Burn Injury Database (iBID) has been in place. Setting: Data from the iBID for the years 2003–2011 were used for a retrospective descriptive observational study of specialised services workload and admissions in England and Wales. Participants: All patients who have been visited or admitted to the burn injury specialised health service of England and Wales during the time period 2003–2011. Data cleaning was performed omitting patients with incomplete records (missingness never exceeded 5%). Outcome measures: Workload, admissions, mortality, length of stay (LOS), geographical distribution, sex differences, age differences, total burn surface area, mechanism of Injury. Results: During 2003–2011, 81 181 patients attended the specialised burn service for assessment and admission in England and Wales. Of these, 57 801 were admitted to the services. Males accounted for 63% of the total workload in specialised burn injury services, and females for 37%. The median (IQR) burn surface area was 1.5% (3.5%). The most frequent reason for burn injury was scald (38%). The median (IQR) age for all the referred workload for both genders was 21 (40). The overall mortality of the admitted patients was 1.51% and the median (IQR) LOS was 1 (5) days. Conclusions: Mortality from burn injuries in England and Wales is decreasing in line with western world trends. There is an observed increase in admissions to burn services but that could be explained in various ways. These results are vital for service development and planning, as well as the development and monitoring of prevention strategies and for healthcare commissioning.